Theology and Chronic Pain: Some Initial Reflections - Creamer, Deborah Beth (Journal of religion, disability & health, 2013)
Chronic pain has received little attention within the academic study of disability and religion. This is a significant loss not only because pain is a common embodied experience but also because reflection on pain offers valuable challenges to existing models of disability: pain does not connect neatly to advocacy work and does not fit well within social and minority understandings of disability, and even medical understandings of pain are inadequate. This essay reflects on pain as a source of knowledge and a way of knowing that is relevant for theological and ethical reflection, particularly within disability and embodiment theologies.